Problem-posing research in mathematics education: A bibliometric analysis - Meral Cansız Aktaş (Journal of Pedagogical Research, 2022)
The aim of this study is to investigate the trends in research related to problem posing in mathematics education. The study focuses on the articles on problem posing in the Web of Science database between 1990 and 2021. The term co-occurrence map, which was created depending on the data in the text with the bibliometric analysis of the articles on problem posing that met the specified criteria, revealed a four-cluster structure according to the degree of relations between the terms. These clusters are called effect (the effect of problem posing on various variables), creativity (the relationship between problem posing and creativity), construct (understandings of how it is thought in the problem posing process and the nature of problem posing) and intervention (opportunities provided by changing existing teaching by including problem posing). This study provides evidence on trends in problem posing related studies. Knowing the research trends on this issue will help researchers obtain information about the areas where more research is needed and plan their future work in that direction.